The effect of case nodes in problem-based learning on the length and quality of discussion: A 2x2 factorial study - Fong, Sheri FT; Sakai, Damon H; D'Eon, Marcel; Trinder, Krista (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Background: Problem-based learning (PBL) relies heavily on case structure for their success. To make more meaningful cases, faculty introduced a “case node” that requires students to make a group decision on the action they will take at a given point in the case. The purpose of this study was to determine whether case nodes enhance PBL discussions.Methods: Two PBL cases were designed with and without a node. In 2011, 2012, and 2015, first-year medical students were assigned one PBL case with a node and one without a node. In total, 26 groups processed cases with a node while 27 groups processed the same cases without the node. All sessions were audio recorded and analyzed to determine the length and quality of discussions.Results: Groups with a node, regardless of case (M = 25.62, SD = 12.25) spent significantly more time in discussion on the node topic than those without a node (M = 16.54, SD = 10.33, p = .005, d = .80). Groups with a node, regardless of case (M = 14.38, SD = 8.04) expressed an opinion significantly more frequently than those without a node (M = 6.07, SD = 5.80, p < .001, d = 1.19).Conclusions: Case nodes increased both the length and depth of discussion on a topic and may be an effective way to enhance case-based instruction.